Inter-cultivar variations of phosphorus deficiency stress tolerance in hydrponically grown Brassica - Kurimoto Hiroyuki; M.H. Rashid khan; Maqsood A. Gill; Adachi Tadashi; Murata Yoshiyuki; Oki Yoko; Akhtar M. Shahbaz (Songklanakarin Journal of Science and Technology (SJST), 2006)
Phosphorus (P) plays a central role as reactant and effector molecule in plant cell metabolism but P is limiting for crop yield on >30% of the world's arable land. Fear of depletion of world reserves of rock P, consistently increasing prices of phosphate fertilizers coupled with their notoriously low utilization efficiency has made the P-application cost ineffective and unacceptable choice for amelioration of inorganic phosphate (Pi) deficiency. A solution culture experiment was conducted to evaluate ten Brassica cultivars for their relative efficiency to utilize deficiently (20 μM) and adequately (200 μM) supplied P, in Johnson's modified solution. Pi deficiency markedly reduced shoot dry matter (SDM), root dry matter (RDM) production. Control of whole plant dry matter by plant P content under P deficient conditions suggests an internal regulation in addition to the influence exerted by external P supply. There were large differences of plant growth among Brassica cultivars exposed to the same P concentration in the growth medium. The cultivars differed significantly (p<0.001) in their root, shoot growth and root to shoot ratio. The P concentrations and uptake in shoot and P utilization efficiency (PUE) also varied significantly among different Brassica cultivars. Shoot and root dry matter yields as well as total biomass production were found to have significant (p<0.01) relationships with their shoot P uptake and P utilization. Cultivars, which were efficient in both P-acquisition and P-utilization, were found to be effective in the production of more biomass under both adequate and deficient levels of P.